Cartografia do trabalho na cidade-floresta - Agenor Sarraf Pacheco (Nepan editor, 2013)
This article is intended to map movements and senses undertaken by rural and forestal inhabitants from the city of Melgaço who work with barrows. Melgaço is located in the archipelago of Marajó, in the Brazilian State of Pará. To achieve this goal, oral memories from those migrant workers, captured in interviews, interact with concepts of oral, social and culture history. It is done so to put in evidence experiences of work, negotiations and political struggles that re-signified ways of life in this city-forest in the last decade of the twentieth century.